The Discovery and Structure‐Activity Evaluation of (+)‐Floyocidin B and Synthetic Analogs. (17th November 2021) - Kleiner, Yolanda; Pöverlein, Christoph; Klädtke, Jannike; Kurz, Michael; König, Henrik F.; Becker, Jonathan; Mihajlovic, Sanja; Zubeil, Florian; Marner, Michael; Vilcinskas, Andreas; Schäberle, Till F.; Hammann, Peter; et al.
Abstract: Tuberculosis represents one of the ten most common courses of death worldwide and the emergence of multidrug‐resistant M. tuberculosis makes the discovery of novel anti‐tuberculosis active structures an urgent priority. Here, we show that (+)‐floyocidin B representing the first example of a novel dihydroisoquinoline class of fungus‐derived natural products, displays promising antitubercular hit properties. (+)‐Floyocidin B was identified by activity‐guided extract screening and its structure was unambiguously determined by total synthesis. The absolute configuration was deduced from a key synthesis intermediate by single crystal X‐ray diffraction analysis. A hit series was generated by the isolation of further natural congeners and the synthesis of analogs of (+)‐floyocidin B. Extensive biological and physicochemical profiling of this series revealed first structure‐activity relationships and set the basis for further optimization and development of this novel antitubercular scaffold. Abstract : Anti‐TB hit series : Our search for new antitubercular natural products resulted in the discovery of the novel epoxyquinone (+)‐floyocidin B, which structure was unambiguously determined by total synthesis. Biological and physicochemical profiling of (+)‐floyocidin B and synthetic analogs revealed first structure‐activity relationships and set the basis for further optimization and development of this novel antitubercular scaffold.